Tests of vigour in seeds of Guazuma ulmifolia Lam. - Gonçalves, Edilma Pereira; De Paula, Rinaldo César [UNESP]; Desmatlê, Maria Esmeralda S. P. [UNESP] (Universidade Estadual de Londrina, 2008)
The work had as objective to verify the efficiency of vigour tests for identification of the physiologic potential in four lots of seeds of Guazuma ulmifolia Lam. The study was developed at the Laboratory of Seed Analysis - UNESP, Jaboticabal, SP. Four lots of seeds from three places of São Paulo state were used: lots I and II, collected in the municipal district of Jaboticabal in 2000 and 2001; lot II,: collected in Santa Rita do Passa Quatro and lot IV, Luiz Antonio, both in 2001. To break seed dormancy the seeds used in all the tests were escarified with sulfuric acid during 50 minutes, and washed in running water during 20 minutes. The evoluations were: seed moisture content, germination percentage, first count test, germination speed index and electric conductivity with different numbers of seeds (50, 75, 100) put to soak in plastic containing 50 and 75mL of water, to the temperature at 250C, during for 72 hours. The seeds of the lot originating from lot III, presented physiologic potential superior to the other studied lots. The tests of electric conductivity, first count, and index of germination speed were appropriate for evaluation of the physiologic potential of the lots. For the electric conductivity test other studies are necessary, involving a larger number of lots, seeking the use possibility a pattern vigour test, while the tests of first count and index of germination speed were appropriate for evaluation of the vigour.
Testes de vigor em sementes de Guazuma ulmifolia Lam.
Keywords: Electric conductivity; Forest seeds; Physiologic potential